To protect, serve, and keep the peace?: the influence of police on civil war - McCormick, Shon A. (Kansas State University, 2013)
This dissertation advances the study of civil war by addressing the means through which states’ police forces may affect the probability of civil war onset. I improve upon extant work on civil war and state capacity by considering the ability of police to act autonomously from the state and operate as a distinct element of the state’s security sector. The project consists of four substantive chapters. One chapter addresses the role of police capacity in preventing civil war and determines that simple measures of police strength do influence the probability of civil war onset. Also, anocracies require a greater number of police to prevent civil war. The next chapter tests whether police repression could lead to civil war by creating grievances among the populace. Tests of this hypothesis determine that while police repression can increase the probability of civil war, it is not as powerful a predictor as state repression overall. The third chapter looks at the effect of the mode of organization of police forces and contains two contrasting hypotheses. The first proposes that police force centralization increases the probability of civil war onset by increasing the likelihood that the state and police view the utility of employing repression more favorably. The other proposes that centralization reduces the probability of civil war onset by making the police more effective. Nevertheless, neither hypothesis yields significant outcomes when tested. The final chapter employs two case studies about the experience of police serving as military during a civil war. I find that in both cases, police service in what are typically military functions did tend to make the police more repressive after the war, which contributed to reoccurrence by giving dissidents a cause around which to rally and by reducing the dissidents’ perceptions of the utility of non-violent means of protest. I conclude the study with a summary of the major findings, suggestions for further study, and recommendations for policy makers.
Keywords: Police; Civil War; Repression; Peace Studies (0563)